2018
DOI: 10.3847/1538-4357/aaa410
|View full text |Cite
|
Sign up to set email alerts
|

Compton-thick AGNs in the NuSTAR Era

Abstract: We present the 2-100 keV spectral analysis of 30 candidate Compton-thick-(CT-)active galactic nuclei (AGNs) selected in the Swift-Burst Alert Telescope (BAT) 100 month survey. The average redshift of these objects is z 0.03 á ñ ~, and they all lie within ∼500 Mpc. We used the MyTorus model to perform X-ray spectral fittings both without and with the contribution of the Nuclear Spectroscopic Telescope Array (NuSTAR) data in the 3-50 keV energy range. When the NuSTAR data are added to the fit, 13 out of 30 of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 69 publications
(108 reference statements)
6
88
1
Order By: Relevance
“…The background region is centered on (J2000) RA = 22:07:03.54 (331°45 53.00 ), decl. = +10:13:42.78 (10°13 42.78 ) with a radius of 10 .power-law photon index Γ = 1.9 (based on the NuS-TAR/XMM best fits,Marchesi et al 2018; and consistent with, e.g.,Risaliti et al 2000;Levenson et al 2006;Hernández-García et al 2015;Ricci et al 2015;Koss et al 2016), plus a gaussian emission line constrained to an energy range surrounding the Fe Kα 6.4 keV line, with constant galactic absorption (4.5 × 10 20 cm −2 ;Levenson et al 2006). This simple power-law plus line model is consistent with the model components utilized in previous spectral fits of NGC 7212 (e.g., ASCA,Risaliti et al 2000; XMM, Guainazzi et al 2005;Hernández-García et al 2015; CXC, Levenson et al 2006;Hernández-García et al 2015; NuSTAR, Koss et al 2016;Marchesi et al 2018), for which the median photon index is Γ ∼ 1.9 and the median equivalent width of the Fe Kα line is EW ∼ 0.8 keV.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The background region is centered on (J2000) RA = 22:07:03.54 (331°45 53.00 ), decl. = +10:13:42.78 (10°13 42.78 ) with a radius of 10 .power-law photon index Γ = 1.9 (based on the NuS-TAR/XMM best fits,Marchesi et al 2018; and consistent with, e.g.,Risaliti et al 2000;Levenson et al 2006;Hernández-García et al 2015;Ricci et al 2015;Koss et al 2016), plus a gaussian emission line constrained to an energy range surrounding the Fe Kα 6.4 keV line, with constant galactic absorption (4.5 × 10 20 cm −2 ;Levenson et al 2006). This simple power-law plus line model is consistent with the model components utilized in previous spectral fits of NGC 7212 (e.g., ASCA,Risaliti et al 2000; XMM, Guainazzi et al 2005;Hernández-García et al 2015; CXC, Levenson et al 2006;Hernández-García et al 2015; NuSTAR, Koss et al 2016;Marchesi et al 2018), for which the median photon index is Γ ∼ 1.9 and the median equivalent width of the Fe Kα line is EW ∼ 0.8 keV.…”
supporting
confidence: 57%
“…The origin of the diffuse emission is likely ionizing radiation from the active nucleus, e.g., from the corona, propagating to large scales via interactions with the interstellar medium (ISM). Georgantopoulos & Akylas (2019) fit a torus model to NuSTAR observations of NGC 7212 using MYTorus 16 and found the best-fit parameters N H = 1.1 × 10 24 cm −2 (consistent with Marchesi et al 2018), E cut > 56, kT = 41 keV.…”
Section: Radial Profiles and Fwhmmentioning
confidence: 77%
“…The only two spectral bands where the obscuring material is optically thin up to high column densities are the hard X-rays ( 15 keV) and the mid-infrared (5 − 50 µm). Thanks to its unprecedented sensitivity covering the 3−79 keV band, NuS-TAR is playing a key role in identifying the missing fraction of CTAGN and determining their properties (e.g., Koss et al 2016;Marchesi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This may potentially add possibly non-negligible systematic uncertainties to the statistical ones. Interestingly, Marchesi et al (2018) analyzing 30 local candidate CT AGN selected from the Swift/BAT 100 month survey, found that the addition of NuSTAR data allowed a re-classification of ∼40% of the sources as Comptonthin. Source variability may furthermore play a role, because these surveys have gathered data over timescales of years (e.g., Lanzuisi et al 2014).…”
Section: Sifting Through Candidate Ct Sourcesmentioning
confidence: 99%